Idel, M., Cábala hebrea y cábala cristiana. Buenos Aires, Editorial Prometeo, 2011, 112 pp. ISBN: 978-98-7574-517-9 - Fredericksen Neira, Alfredo (’Ilu. Revista de Ciencias de las Religiones, 2022)
Reseña de la obra de Idel, M., Cábala hebrea y cábala cristiana. Buenos Aires, Editorial Prometeo, 2011, 112 pp. ISBN: 978-98-7574-517-9.